Carcass and meat traits, and non-carcass components of lambs fed ration containing increasing levels of urea - Sandra Rozanski (Semina: Ciências Agrárias, 2017)
The objective of this study was to evaluate the carcass and meat traits, and the non-carcass components of crossbred Dorper lambs fed diets with increasing levels of urea (0.0, 0.5, 1.0, and 1.5% of dry matter – DM). The experimental design was completely randomized with four treatments (urea inclusion levels) and six replicates per treatment. Lambs were fed ad libitum for 56 days and slaughtered at 37.9 ± 5.1 kg of body weight (BW). The weight and yield of carcass before and after cooling were not inÀuenced by urea levels, with average values of 16.9 kg and 44.6% for cold carcass weight and yield. Urea levels did not affect the morphometric measurements, the fat deposition on the carcass, the weight of carcass cuts and the weight of non-carcass components. There was a quadratic effect of urea levels on the loin yield, which may achieve maximum value of 11.31% with the inclusion of 0.84% DM urea in the feed. The pH and the color coordinates L* (brightness), a* (red intensity) and C* (saturation) of the meat also showed quadratic response to the urea levels, where in the minimum value of 5.53 for pH, maximum value of 48.67 for L* and minimum values of 14.04 and 16.21 for a* and C* may be obtained by including 0.53 to 0.70% DM urea in the ration. The inclusion of 0.84% DM urea in the ration is recommended to obtain maximum yield of loin and meat with attractive characteristics to the consumer, which is characterized by high red intensity and brightness. If consumers have preference for lamb meat with a more intense red color, the inclusion of 1.5% DM urea should be considered in the ration formulation.